The complete guide to drawing and illustration a practical and inspirational course for artists of all abilities - Gray, Peter (London Arcturus Publishing Limited, 2006)
This volume will demystify the subject and, at every stage, treat drawing as a rewarding activity that encourages observation, experimentation and play.
The first marks -- Objects & observation -- Nature's landscape -- Going to town -- Making faces -- The human figure -- Creating characters -- The animal kingdom.
Keywords: Drawing -- Technique; Illustration of books